2020
DOI: 10.1111/vde.12835
|View full text |Cite
|
Sign up to set email alerts
|

In vitro killing of canine strains of Staphylococcus pseudintermedius and Escherichia coli by cefazolin, cefovecin, doxycycline and pradofloxacin over a range of bacterial densities

Abstract: Background -Bacterial densities likely fluctuate during infection and may exceed the bacterial density used in susceptibility testing. As such, investigation of bacterial killing by antibiotics over a range of varying bacterial densities may provide important differences between compounds and could impact drug selection for therapy.Hypothesis/Objectives -To measure killing of clinical isolates of Staphylococcus pseudintermedius and Escherichia coli by cefazolin, cefovecin, doxycycline and pradofloxacin at clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…These values serve as a guide for dosing concentrations that can potentially reduce the amplification of bacterial subpopulations with reduced susceptibility to antimicrobials. The determination of MPC and MIC values provides valuable information regarding the effectiveness of these antibiotics against the specified pathogens [53]. Critical Concentration (Ccr) is the minimum concentration of an antibiotic that is required to prevent microbial growth and inhibit the concentration from reaching a specific critical point.…”
Section: Minimum Bactericidal Concentration (Mbc) Valuesmentioning
confidence: 99%
“…These values serve as a guide for dosing concentrations that can potentially reduce the amplification of bacterial subpopulations with reduced susceptibility to antimicrobials. The determination of MPC and MIC values provides valuable information regarding the effectiveness of these antibiotics against the specified pathogens [53]. Critical Concentration (Ccr) is the minimum concentration of an antibiotic that is required to prevent microbial growth and inhibit the concentration from reaching a specific critical point.…”
Section: Minimum Bactericidal Concentration (Mbc) Valuesmentioning
confidence: 99%
“…When used in randomised clinical trials to treat dogs with superficial or deep pyoderma, cefovecin was shown to have a high clinical efficacy similar to previously used antibiotics, with only a small percentage of dogs showing adverse symptoms [ 88 ]. Although these results indicate that cefovecin is a safe and effective newly synthesised antimicrobial for veterinary use in particular geographical locations, the use of cefovecin is restricted only to use in cats and dogs where antibiotic sensitivity testing indicated use is required; therefore, additional research has focused on repurposing multiple human antibiotics for use in animals [ 89 , 90 , 91 ]. Many studies have tested the efficacy of various human antibiotics including nitrofurantoin, rifampicin, doxycycline, cefazolin and linezolid in the treatment of S. pseudintermedius infections in canines, mainly pyoderma, UTIs and surgical site infections [ 89 , 90 , 91 ].…”
Section: Current and Future Treatment Options For Staphymentioning
confidence: 99%
“…Although these results indicate that cefovecin is a safe and effective newly synthesised antimicrobial for veterinary use in particular geographical locations, the use of cefovecin is restricted only to use in cats and dogs where antibiotic sensitivity testing indicated use is required; therefore, additional research has focused on repurposing multiple human antibiotics for use in animals [ 89 , 90 , 91 ]. Many studies have tested the efficacy of various human antibiotics including nitrofurantoin, rifampicin, doxycycline, cefazolin and linezolid in the treatment of S. pseudintermedius infections in canines, mainly pyoderma, UTIs and surgical site infections [ 89 , 90 , 91 ]. Whilst studies did show that the use of such human antibiotics was effective in vitro against clinical isolates or was able to treat the infection of interest in clinical trials, it is important to note that some of these antibiotics resulted in adverse side effects and possessed a short half-life in serum, therefore requiring frequent and repeated doses, which is known to increase resistance [ 89 , 90 , 91 ].…”
Section: Current and Future Treatment Options For Staphymentioning
confidence: 99%
See 2 more Smart Citations